Factor Structure of the Klein Sexual Orientation Grid Among Latina/o/x Adolescents - Lozano, Alyssa; Ocasio, Manuel A; Brincks, Ahnalee; Harkness, Audrey; Perrino, Tatiana; Prado, Guillermo (International journal of LGBTQ+ youth studies, 2025)
Measuring sexual orientation involves assessing multiple domains to account for the various conceptualizations adolescents may have. The purpose of this study was to examine: (1) the factor structure and reliability of the Klein Sexual Orientation Grid (KSOG) and (2) measurement invariance across age and nativity groups. Participants included 454 Latina/o/x adolescents [25.3% Latina/o/x sexual minority youth (LSMY) and 74.7% Latina/o/x non-SMY]. We examined the hypothesized factor structure of the KSOG using confirmatory factor analysis and the configural, metric, and scalar invariance of the identified factor structure was examined between age (12-14 and 15-17) and nativity (U.S. born and foreign-born) groups. A single factor captured: identity, attraction, emotional connection, and fantasies (CFI/RMSEA=1.00/.000). We found evidence for metric noninvariance suggesting that sexual orientation as a latent construct does not perform equivalently among Hispanic adolescents who are younger versus older (Δχ (3) = 106.01, < 0.001, ΔCFI = 0.041, ΔTLI = 0.064, and ΔRMSEA = 0.154) or adolescents who are U.S. born versus foreign-born (Δχ (3) = 10.34, < 0.05, ΔCFI = 0.003, ΔTLI = 0.002, and ΔRMSEA = 0.011). The KSOG may not be used equivalently among older and younger Latina/o/x adolescents and Latina/o/x adolescents who are U.S. born and foreign-born.